2020
DOI: 10.21474/ijar01/11956
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Scanning Systems - A Current Overview

Abstract: Intraoral scanners (IOSs) are devices used for capturing direct optical impressions in dentistry. IOS eliminates the errors that are encountered with the conventional impression making procedures. The last decade has seen an increasing number of optical IOS devices, and these are based on different technologies. The objective of this review article is to discuss intraoral scanners with regards to its technology, generation systems, scanning paths, necessity of a powdering medium, accuracy (Trueness and precisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Special processing software generates point clouds, meshes, and 3D coordinates (XYZ axis). These point clouds and meshes are aligned and fused, culminating in a 3D reconstruction of the scanned object (Marques et al., 2021; Zimmermann et al., 2015). Consistent with preceding studies, our research found no significant differences in the overall 3D deviation between the IOS and CI techniques (Marshaha et al., 2023; Papaspyridakos et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Special processing software generates point clouds, meshes, and 3D coordinates (XYZ axis). These point clouds and meshes are aligned and fused, culminating in a 3D reconstruction of the scanned object (Marques et al., 2021; Zimmermann et al., 2015). Consistent with preceding studies, our research found no significant differences in the overall 3D deviation between the IOS and CI techniques (Marshaha et al., 2023; Papaspyridakos et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The field of view effect is the most important reason for low accuracy of IOSs reported in the literature. Evidence shows that the larger the area scanned by IOS, the greater the errors of digital impressions could be; such large errors are due to the cumulative effects of scanning errors (Zimmermann et al, 2015 ). Also, different IOSs may have different levels of accuracy (Takeuchi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%